ATRIBUT PRODUK DALAM MENINGKATKAN LOYALITAS PELANGGAN (studi pada Gorontalo Post) - Herlinda Mansur; Deby Rita Karundeng; Mohamad Afan Suyanto (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This study uses a quantitative approach emphasizing the analysis on numerical data that is processed by statistical methods. This study aims to determine and analyze the effect of product attributes, including product quality, design, brand, price and service, simultaneously and partially influence customer loyalty in Gorontalo Post newspaper and analyze the dominant variables affecting customer loyalty. The research results obtained are Simultaneously product attributes consisting of product quality, product style and design, product prices, product brands, product services have a positive and significant influence on customer loyalty Gorontalo Post. Partially, each of the independent variables studied, namely product quality, product style and design, product price, product brand, product service has an influence on Gorontalo Post customer loyalty. The dominant indicator in the formation of product quality is the indicator of completeness of news. The dominant indicator in shaping the style and design of Gorontalo Post products is the polite language style indicator. Indicators that have a dominant contribution in product prices are indicators of price conformity with quality. The dominant indicator in shaping the product brand in Gorontalo Post is the easily recognizable brand indicator. The dominant indicator in shaping the Gorontalo Post product service is the Gorontalo Post delivery indicator that is always on time. The product quality variable applied by Gorontalo Post has the most dominant effect on customer loyalty.